Una propuesta de reconstrucción del Retablo de las Ánimas de la iglesia de San Miguel de Peñafiel - Martín Ansón, María Luisa (Anuario del Departamento de Historia y Teoría del Arte, 1998)
This article deals with the restoration in its initial state of an altarpiece belonging to the palentian scope with Burgos influence of the first third of the XVIth century, profoundly altered in the XVIIIth century. Some of panels included in the present altarpiece are related to the primitive high altarpiece and the Master of Osma. Likewise, the frequent practice of obtaining inspiration in engravings for the design of the scenes is clearly shown.